2017
DOI: 10.3389/fphar.2017.00446
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Emodin Derived Glutathione Adduct in Normal Rats Administered with Large Dosage of Polygoni Multiflori Radix

Abstract: Polygoni Multiflori Radix (PMR) has been commonly used as a tonic in China for centuries. PMR-associated hepatotoxicity has been drawing increasingly more attention in recent years in parallel with its wide utilization. Anthraquinones (AQs) are recognized as the main hepatotoxic components in PMR. However, the exact underlying mechanism of AQs poisoning is still not fully understood. Herein, we proposed a hypothesis that metabolic activation of AQs such as emodin was involved in PMRinduced liver injury, AQs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 43 publications
2
13
0
Order By: Relevance
“…Analysis of serum samples from rats in the control and emodin groups indicated that emodin induced liver injury (Yang et al, 2018). Previous studies have also found that emodin induced liver injury in vivo and in vitro to some extent (Li et al, 2012;Zhang et al, 2010;Liu et al, 2015b;Ma et al, 2015;Jiang et al, 2017), similar to our observation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Analysis of serum samples from rats in the control and emodin groups indicated that emodin induced liver injury (Yang et al, 2018). Previous studies have also found that emodin induced liver injury in vivo and in vitro to some extent (Li et al, 2012;Zhang et al, 2010;Liu et al, 2015b;Ma et al, 2015;Jiang et al, 2017), similar to our observation.…”
Section: Discussionsupporting
confidence: 91%
“…In the down-regulated proteins, 11 proteins related to redox regulatory were found (Table S6), which increased susceptibility to oxidative stress and contributed to the disruption of redox homeostasis and ultimately damaged biomolecules (Liu et al, 2009). Previous studies have found that emodin could induce oxidative stress by producing ROS and consuming antioxidants such as GSH and SOD (Ma et al, 2015;Jiang et al, 2017;Jiang et al, 2018). However, in this study, emodin could inhibit Prdx, Gpx, thioredoxin system and glutaredoxin system, which is a new discovery.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In addition, the reactive metabolite overproduction depletes GSH, which could result in hepatotoxicity [ 102 104 ]. Research also found that emodin could conjugate with GSH, forming emodin-GSH and depleting GSH in PM-induced liver injury rats [ 40 – 42 ]. An increasing number of studies have shown that mitochondrial damage may be a factor and pathway that predisposes individuals to PM-induced liver injury.…”
Section: Hepatotoxic Mechanism Of Pmmentioning
confidence: 99%
“…It is widely accepted that cytochrome P450 (CYPs)-mediated metabolic activation is responsible for the hepatotoxicity of some natural products ( Njuguna et al, 2012 ; Ruan et al, 2014 ; Lin et al, 2016 ) via the formation of reactive electrophilic intermediates that react with nucleophilic sites of macromolecules, such as protein ( Xia et al, 2016 ), glutathione ( Jiang L.L. et al, 2017 ), and nucleic acid ( Yu et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%